Behavior Management Using Arithmetic Puzzle Distraction During Primary Tooth Pulpotomy: A Case Report Of A 10-Year-Old Child - Sintia Nora; Septriyani Kaswindiarti (CV. AFDIFAL MAJU BERKAH, 2026)
Behavior management is a crucial component in the success of pediatric dental care. Distraction as a non-pharmacological technique plays an important role in reducing anxiety and improving patient cooperation. Arithmetic puzzles represent an active form of distraction that engages children’s cognitive abilities; however, their application in invasive procedures such as pulpotomy has rarely been reported. A 10-year-old boy presented with dental caries in the mandibular right primary second molar (tooth 85) and was planned for pulpotomy treatment. The patient exhibited dental anxiety toward dental procedures, requiring a behavior management approach. Behavior management was implemented using a combination of Tell–Show–Do, desensitization, active distraction with an arithmetic puzzle, and positive reinforcement at each visit. After the patient adapted to the clinical environment and demonstrated improved cooperation, conventional pulpotomy was performed according to clinical standards, followed by temporary restoration. Consistent application of behavior management techniques improved communication, built patient trust, reduced anxiety, and enhanced cooperation throughout treatment. The arithmetic puzzle served as an active distraction by engaging cognitive processes appropriate for the developmental stage of school-aged children, thereby shifting attention away from dental procedures. The arithmetic puzzle has potential as a simple, cost-effective, and practical distraction method to improve pediatric patient cooperation during dental treatment. Further studies with larger sample sizes and standardized behavioral assessment tools are required to objectively evaluate its effectiveness.